Content-based instruction. A closer look at CBI in Iceland. - Tinna Eyjólfsdóttir (2011)
In this essay Content-based instruction is examined; a foreign language teaching approach that is becoming widely used throughout the world, where teaching a language and teaching content is combined. Aspects of the approach are discussed and its effectiveness in Iceland is explored, as well as whether or not it has an affect on the first language. Is this approach effective as a means of learning both language and content? Is it a realistic option in Iceland? Does it affect the first language? These are some of the questions explored in this essay. In addition, a qualitative study of the application of Content-based instruction within the International School of Iceland is examined and discussed. Students and a teacher were interviewed about the use of English in the classroom and their attitudes towards it.